Oztag: high risk for hand injuries?. Issue 7 (15th September 2015) - Raymond, Andrew; Harish, Varun; Merten, Steve
Abstract: Background: Oztag is an Australian tag rugby code in which opponents are 'tackled' by removing Velcro tabs from their shorts. It is assumed to be safer than other higher‐contact rugby codes. Methods: Oztag‐related hand injuries were identified by a word search of the electronic emergency department records of Concord Repatriation General Hospital from January 2011 to October 2013. Clinical records were retrospectively reviewed. Results: Twenty‐eight presentations were identified. Mean age of patients was 24 years (range 13–38). Injuries included fractures, dislocations and ligamentous injuries, in isolation or combination. The most common injuries were middle phalangeal fractures (six), all of which required operative fixation. No tendon avulsions were identified. The most common mechanism of injury was attempted tackle, which was much more likely to require operative management than any other mechanism (70% versus 14%, P = 0.010). Conclusions: While the prevalence of Oztag‐related hand injuries may be low, the occurrence of potentially debilitating injuries in a young, working population raises concern. The 'tag' tackle, which involves players running at speed with outstretched fingers, is particularly high risk. Prospective audit of injuries is required and players and organizers should be made aware of the dangers of this 'low‐contact' sport.